Instituteʼs of reading communication resources in the digital age - Oleshko, Vladimir F.; Oleshko, Yevgeny V. (Journal of the Belarusian State University. Journalism, 2020)
The problem of the significance of reading as a socio-cultural institution is considered. Today, reading-this traditional, centuries-old form of everyday intellectual activities in the context of self-development of individuals, is experiencing serious problems, primarily due to the widespread digitalisation of mass media content. The transformation of technologies and practices for the production of multimedia texts should not, as it is proved, push the meaning-value components of modern mass media activity into the background. And it is through the use of communicative reading resources in general and systematic work to promote individual high-quality texts, in particular, that the functions of journalism can be successfully implemented even in the digital age. This type of social activity contributes to the free spiritual unity of people, which can only be achieved under the influence of art, literature and argumentative journalism. Using the data of their sociological research, the authors conclude that the principles of «attracting, not retaining attention», «pictorial, not meaning-making», which are followed today by many mass media, as well as most subjects of information activity in social networks, do not contribute to the personal and intellectual development of mass audience members. After all, intentions are most often caused by economic dominants and reflect only the current agenda. Consequently, this brings to the fore the problem of developing practical skills through the Institute of reading, especially for young generations, to work with voluminous, informational and conceptually rich texts of printed and online publications. In the intergenerational cultural and civilizational interaction Institute for reading is an important communicative resource, as it plays a bridging role, shaping not only the dialogue relations, but also implements specific, needed more than ever today, media education learning technologies text twist, conflict manipulation, and the ability to identify the main, essential in ever-increasing volume of information flow.
Keywords: reading; digital age; culture; information; mass media; meaning-making; communicative and cultural memory